Predictors of pulmonary involvement in patients with extra-pulmonary tuberculosis - Malak M El-Hazmi; Fawzia E Al-Otaibi (Wolters Kluwer Medknow Publications, 2012)
Objectives: The aim of this study is to assess the value of chest radiographs (CXRs) and sputum examinations in detecting pulmonary involvement of tuberculosis (TB) in patients with extra-pulmonary tuberculosis (EPTB). Materials and Methods: A retrospective analysis was performed among 248 EPTB patients with culture-proven diagnosis of tuberculosis seen between January 2001 and December 2007 at a tertiary teaching hospital, Riyadh, Saudi Arabia. Demographics, clinical, laboratory and radiological findings were reviewed and assessed. This study was approved by the hospital ethics and research committee. Results: One hundred twenty five of 233 EPTB patients (53.6%) had abnormal CXR findings. There was a significant difference in the occurrence of positive sputum culture results between patients with abnormal CXR findings (30/57) and those with normal CXR findings (4/17) (P = 0.04). Of 17 HIV-negative/unknown HIV-status EPTB patients with normal CXR results, 4 patients (23.5%) had positive sputum culture results. Intrathoracic lymphadenopathy (P < 0.001), pleural TB (P < 0. 001) and disseminated TB (P = 0.004) were associated with an increased risk of abnormal CXR findings. Patients with cough (52.9%), weight loss (41.2%) and night sweats (26.5%) are more likely to have positive sputum culture results. Conclusion: CXR findings are predictive of positive sputum culture results. However, the rate of normal CXR among EPTB patients with positive sputum culture results was relatively high. Therefore, respiratory specimen cultures should be obtained in TB suspects with a normal CXR to identify potentially infectious cases of TB.